PENGARUH UKURAN PERUSAHAAN, REMUNERASI CEO DAN MODAL INTELEKTUAL TERHADAP STICKY COST PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR BEI TAHUN 2018-2019 - Verdiana Hendrawati Santoso; Dyna Rachmawati (Jurnal Akuntansi dan Pajak, 2021)
Sticky cost occured when costs increase by the time activity increases, but it does not decrease as fast as it increases when sales decreases. The sticky cost had a bad effect for company where the level of sticky cost is increase company will more difficult to achieve the level of profit. This study aims to analyze and examine the effect of company size, CEO remuneration and intellectual capital on sticky costs. The population of this research is the manufacture companies listed on the Indonesia Stock Exchange (BEI) in 2018-2019. The total samples of this research are 56 companies were selected using purposive sampling method. The data analysis technique used multiple linear regression analysis. The results of the research show that company size have a significant negative effect on sticky costs, the company with a large size can manage costs properly to minimize the sticky costs, while CEO remuneration has a positive effect on sticky costs, the higher the amount of remuneration will increase the total selling, general administrative (SG&A) cost that triggers sticky cost, and intellectual capital has no effect on sticky costs, the greater or the smaller the intellectual capital investment will not triggers sticky costs.